Preliminary Report of Literature Review on Understandings of Interdisciplinary and Transdisciplinary Research - Wallace, Doireann; Vienni Baptista, Bianca; Maryl, Maciej; Wciślik, Piotr; Fletcher, Isabel; Buchner, Anna; Pohl, Christian (My University, 2019)
This report presents emerging findings from a literature review being undertaken as part of the SHAPE-ID Horizon 2020 project (https://www.shapeid.eu), which addresses the challenge of improving interdisciplinary research (IDR) and transdisciplinary research (TDR) between Arts, Humanities and Social Sciences (AHSS) disciplines and other scientific disciplines. The report describes efforts to build a robust sample of literature, aligning qualitative and quantitative methodologies and beginning to map understandings and factors for success and failure in the literature.
Keywords: Interdisciplinarity; transdisciplinarity; interdisciplinary research; transdisciplinary research; arts; humanities; social sciences; integration; understandings; International Integration; Interdisciplinary research; RESEARCH POLICY IMPLICATIONS; interdisciplinary collaboration; transdisciplinary collaboration